2014
DOI: 10.1177/0956797614533801
|View full text |Cite
|
Sign up to set email alerts
|

Visual Environment, Attention Allocation, and Learning in Young Children

Abstract: A large body of evidence supports the importance of focused attention for encoding and task performance. Yet young children with immature regulation of focused attention are often placed in elementary-school classrooms containing many displays that are not relevant to ongoing instruction. We investigated whether such displays can affect children's ability to maintain focused attention during instruction and to learn the lesson content. We placed kindergarten children in a laboratory classroom for six introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
149
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(172 citation statements)
references
References 28 publications
18
149
0
5
Order By: Relevance
“…These findings support Fisher et al (2014) who showed that young TD children displayed more offtask behaviour, specifically more looking at information on the walls of the lab classroom, when the physical environment was heavily decorated. We extend this by showing this effect in TD children across a broader age range (5 to 13 years), indicating that the impact of visual displays in the classroom is not just relevant for young children, but for children throughout the primary school.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…These findings support Fisher et al (2014) who showed that young TD children displayed more offtask behaviour, specifically more looking at information on the walls of the lab classroom, when the physical environment was heavily decorated. We extend this by showing this effect in TD children across a broader age range (5 to 13 years), indicating that the impact of visual displays in the classroom is not just relevant for young children, but for children throughout the primary school.…”
Section: Discussionsupporting
confidence: 85%
“…Although not associated with performance on the lesson for either group, this is something that should be followed up in future work. Fisher et al (2014) showed that looking at the heavily decorated physical classroom negatively impacted learning. A key question in the current study was whether increased attention to the HVD background impacted children's learning performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations